(3OjhGf (B((3GdGeGe(B) (3Ydj Hf CHj WGdH cQe Gddg hLggs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s ((3eMeO Jbj bGSe Ydj GdNhGfSGQj s)
(3ChdgG (B:s
(3ddg GdMeO Ydi fYeg hEeG Ydi fbeg JOaY JTGA aJaYd eG TFJg hJSeY ef MjK dG fSeY s
(3BNQgG (B:s
(3JhSd HGdfHj acd NWH jghf EPG JhSd HGdfHj hdG JLRY EPG eG fGH NWH ace ddg ef dWa Naj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B160 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B802s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(896) s
Keywords: (3GdCOHs